Trophic interactions of an invasive gecko in an endemic-rich oceanic island: Insights using DNA metabarcoding - Martins, Beatriz; Silva-Rocha, Iolanda; Mata, Vanessa A.; Gonçalves, Ysabel; Rocha, Ricardo; Rato, Catarina (Frontiers in Ecology and Evolution, 2022)
Understanding the trophic interactions of introduced predators is key for evidence-based management of biological invasions. This is particularly important in oceanic islands, where predator-prey networks often include numerous endemic and range-restricted species. Geckos are successful island colonizers and in recent years numerous species have established populations in a wide array of oceanic islands. One such species is the Moorish gecko (Tarentola mauritanica), which has colonized multiple islands across the Mediterranean basin, Caribbean and Macaronesia. The species was first reported in Madeira Island in 1993 and over the last 30 years has colonized most of the islands’ southern coast and expanded to the nearby island of Porto Santo. Here, we used DNA metabarcoding to provide the first insights into the diet of this successful colonizer in its introduced range. The species’ diet was mainly composed of ground-dwelling arthropods belonging to the families Porcellionidae (Isopoda), Julidae (Diplopoda) and Formicidae (Hymenoptera). The diet richness and composition were not affected by neither sex nor size of adult geckos, instead they both change across populations. However, trophic niche-width differed among size classes, with smaller geckos feeding on a wider range of prey. We identified over 160 different Operational Taxonomic Units in the diet of T. mauritanica, with 21.6% of them belonging to introduced invertebrates and 13.6% to native species. Native prey taxa included the endemic Madeira wall lizard (Teira dugesii), the sole native reptile to Madeira. We also detected several agricultural pests and disease vectors in the diet of this exotic predator, and 19 taxa identified as prey had not yet been recorded to Madeira. Of these, several are serious agricultural pests, highlighting how this introduced gecko can be used as a natural sampler, in particular for the early detection of invasive arthropod pests. This study emphasises the importance of trophic studies for monitoring the impacts of introduced predators in fragile insular systems.